Astronomy: the evolving universe - Zeilik, Michael (Cambridge, Cambridge University Press, 2002)
Thoroughly updated and re-conceived, Astronomy: The Evolving Universe, Ninth Edition, equips the introductory astronomy student with the essential tools for understanding the night sky. Michael Zeilik has revised his successful textbook based on recent research in astronomy education. Significantly shorter than the previous edition, the ninth edition is organized into four concept clusters: Cosmic Distances, Heavenly Motions, Celestial Light and Celestial Navigators. Material has been streamlined throughout to make the descriptions, concepts, and explanations clearer. Each chapter ends with a concise summary of the concepts in each cluster. Each chapter contains at least one Celestial Navigator, a map that provides a visual guide of major concepts in the chapter and explicitly shows their connections. Throughout, illustrations have been updated to be clearer and more relevant.
Appendix A-F, 485-497p.
Keywords: Astronomy; Mathematics